Influence of laser radiation on optical properties of high resistivity crystals CdTe and solid solutions Cd1-xZnxTe - Gentsar, P. O.; Levytskyi, S. M. (Physics and Chemistry of Solid State, 2020)
In this paper, the transmission and reflection spectra of single crystals р-CdTe(111) are measured; solid solutions of Cd1-хZnхTe (х=0.1) in the range (0.2 – 1.7)·10-6 m before and after laser irradiation at the wavelength λ = 532 nm in the energy range 66 - 164 mJ/cm2 for CdTe(111) and in the energy range 46.6 mJ/cm2 - 163.5 mJ/cm2 for Cd1-хZnxTe (x = 0.1). It is established that the main mechanism of influence of pulsed laser irradiation on the optical properties of thin surface layers of the investigated crystals is structural gettering, that is, the absorption due to the presence of sections of semiconductors that have a defective structure and have the ability to actively absorb defects and points.